Applied incident response - Anson, Steve (Wiley, 2020)
Incident response is critical for the active defense of any network, and incident responders need up-to-date, immediately applicable techniques with which to engage the adversary.''Applied Incident Response'details effective ways to respond to advanced attacks against local and remote network resources, 'providing proven response techniques and a framework through which to apply them.' As a starting point for new incident handlers, or as a technical reference for hardened IR veterans, this book details the latest techniques for responding to threats against your network, including: -Preparing your environment for effective incident response -Leveraging MITRE ATT & CK and threat intelligence for active network defense -Local and remote triage of systems using PowerShell, WMIC, and open-source tools -Acquiring RAM and disk images locally and remotely -Analyzing RAM with Volatility and Rekall -Deep-dive forensic analysis of system drives using open-source or commercial tools -Leveraging Security Onion and Elastic Stack for network security monitoring -Techniques for log analysis and aggregating high-value logs -Static and dynamic analysis of malware with YARA rules, FLARE VM, and Cuckoo Sandbox -Detecting and responding to lateral movement techniques, including pass-the-hash, pass-the-ticket, Kerberoasting, malicious use of PowerShell, and many more -Effective threat hunting techniques -Adversary emulation with Atomic Red Team -Improving preventive and detective controls.- Resumé vydavatel
Includes index.
Keywords: počítačová bezpečnost; počítačové sítě; zabezpečení počítačových sítí; computer security; computer networks; computer network security; elektronické knihy; monografie; electronic books; monography